A Stela of the Family of Khaemtir (i) and the Scribe Qenherkhepshef (i) (Chicago OIM E14315) - Teeter, Emily.
Oriental Institute stela E14315 was excavated at Medinet Habu in 1928. All four surfaces of the limestone monument are decorated. According to a text on the recto, the stela was commissioned by the Worker in the Place of Truth, Khaemtir (i). Also shown are men who, it is suggested, comprise four generations of his family, including grandchildren, some of whom are not otherwise attested. The scribe Qenherkhepshef appears very prominently on the recto of the stela, and it is proposed that he is shown in this context because the family was beholden to him for their positions. The recto of the stela was carved in approximately year 40 of the reign of Ramesses II. The verso and edges of the stela, it is suggested, were carved two generations later, at the end of the reign, an indication that Qenherkhepshef continued to have the ability to influence the careers of this family of workers and that the family felt it appropriate to honor him on their family monument.